(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to determine the prevalence of poor sleep quality and identify associated factors among high school students in Tay Ninh Province, Vietnam. Methods: A cross-sectional study was conducted at Hoang Le Kha High School for the Gifted, Tay Ninh Province, from February to June 2023. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) scale, and data were analyzed through multivariate logistic regression with a significance level of p < 0.05. Results: A total of 285 students participated in the study, of whom 61.4% reported poor sleep quality. Factors significantly associated with poor sleep quality included being male (OR=0,54; CI 95% = 0,32 – 0,92), experiencing little or no family supervision (OR=3,16; CI 95% = 1,51 – 6,61), belonging to the excellent student team (OR=2,5; CI 95% = 1,02 – 6,34), perceiving their health as poor or average (OR=1,7; CI 95% = 1,07 – 2,71), and feeling anxious about academics (OR =2,2; CI 95% = 1,20 – 3,89). Conclusion: Poor sleep quality is prevalent among high school students in Tay Ninh Province. Addressing this issue requires collaborative efforts between schools and families to provide effective management strategies and psychological support.